2010
DOI: 10.1111/j.1439-0507.2010.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular protease expression in Microsporum gypseum complex, its regulation and keratinolytic potential

Abstract: Two soil isolates of Microsporum gypseum were studied for the production of extracellular proteases. Both the strains secreted protease on glucose-gelatin medium. The enzyme activity peaked on day 15 at 28°C. Asparagine repressed protease yield. Sugars caused catabolite repression of protease formation. Protease activities of both the isolates were significantly affected by incubation period, culture media and carbohydrates used. Both the strains grew on the skin bait and caused a gravimetrically measurable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…55, 56 As shown in Tables 2 and S15, compound 10 retained the activity of 1 , while 7 showed a slight decrease in activity. Compound 10 has previously been reported to retain the activity of 1 against the plant pathogen Botrytis alii , 35 but its activity against dermatophytes, particularly M. gypseum , has not been reported.…”
Section: Resultsmentioning
confidence: 88%
“…55, 56 As shown in Tables 2 and S15, compound 10 retained the activity of 1 , while 7 showed a slight decrease in activity. Compound 10 has previously been reported to retain the activity of 1 against the plant pathogen Botrytis alii , 35 but its activity against dermatophytes, particularly M. gypseum , has not been reported.…”
Section: Resultsmentioning
confidence: 88%
“…This was demonstrated by Mini, et al [ 53 ] and Anbu, et al [ 54 ] in cultures of Aspergillus flavus and Scopulariopsis brevicaulis strains, who reported a decrease in keratinase activity in the presence of glucose and xylose, respectively. Anbu, et al [ 54 ] and Singh [ 55 ] explained this effect by the catabolic repression of proteolytic enzymes by exogenous carbohydrates. Anbu, et al [ 56 ] reported the accumulation of organic sulfur-containing end products as another reason for the inhibition of keratinase activity in fungal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This fact is obviously associated with a better investigation of these organisms as objects of scientific research and biotechnological processes in comparison with fungal models, although filamentous fungi are also capable of secreting hydrolases that destroy keratin [ 21 ]. Most of the accumulated knowledge about fungal keratinases relates to enzymes synthesized by dermatophytes [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], while data on keratinolytic enzymes of micromycetes that do not cause dermatophytosis remain scarce [ 9 , 21 ].…”
Section: Introductionmentioning
confidence: 99%